Exploring social construction experiences through life skills education program during adolescence in Maldives - Nasheeda, Aishath (2020)
The main purpose of this study is to describe young adults’ experiences of life skills education program during their adolescence. The study takes on a retrospective approach so that the respondents can reflect on their experiences of life skills education programs. Hence, the study investigates the social construction of the participants’ experiences through a social psychology lens. In order to explore the experiences of the participants, a narrative research methodology is adopted in understanding the participants’ experiences in the program. Two participants’ experiences were collected through semi-structured interviews. A multimethod restorying framework facilitated in transforming the interview transcripts into stories. The social constructivism in social psychology provides a theoretical basis for understanding how realities and views of the world are individual specific and created through social interactions within the individual social environment. Exploring how the participants have constructed their experience of LSE program through their feelings, thoughts and behaviour helped in understanding how the participants’ interactions during the LSE program translated into meaningful skills in future. Most of the described events evolved around their adolescence, their struggle, achievements and the life skills education program experiences in school. Both Shau and Al’s stories reflected how their adolescence, life skills education experiences and their interactions with their families, schools and friends shaped their lives. The type of experiences that both participants had with the life skills education program were subjective in number of ways such as age of exposure, number of life skills programs, delivery method and also the social environment. Findings of the research suggests that life skill approach is an important approach to transmitting knowledge, attitudes and skills to real life problem situations. However, it is the interactive experiences in the society and its people that shapes the individual’s thinking, attitude and provides a sense of purpose in life. This insight deepens the understanding of the life skills education program and helps in identifying the gaps in delivery of the program. It also signals that there are priorities and concerns regarding the future of LSE program in the Maldives. The study also has implications for stake holder and policy makers in designing, implementing and delivery of age appropriate structured LSE program from early on their adolescence. As this is a process study the findings of the study helps in generating hypothesis for future research in life skills education. It is also important to conduct similar studies to collect stories not only from young adults, but also from high risk adolescents who are already exposed to drugs and smoking to better understand the issues related to them and also the level of transfer of skills in them. Mixed method studies can be conducted to evaluate the program effectiveness and to understand which skills are required most at different stages of individuals’ life.